1995
DOI: 10.1093/treephys/15.7-8.457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gibberellin A4/7, root pruning and cytokinins on seed and pollen cone production in black spruce (Picea mariana)

Abstract: Stem injections of 8-9-year-old black spruce (Picea mariana (Mill.) B.S.P.) trees with gibberellin A(4/7) (GA(4/7)) alone and in combination with root pruning increased both seed and pollen cone production in both 1991 and 1992. Combining GA(4/7) and root pruning produced a larger increase in reproductive bud production than either treatment alone, but the complementary effects were less during the warm dry summer in 1991 than during the wet summer in 1992. Cytokinin applications reduced the stimulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Abscisic acid negatively modulates the effect of other plant hormones, such as GAs (Tompsett 1977) and auxin (Weiss and Ori 2007). This is of interest in conifers, because exogenously applied GA has been proven to be an effective stimulant of cone formation (Ross 1983;Pharis and King 1985;Smith and Greenwood 1995;Kong et al 2008). The main ABA catabolic pathway in many higher plants is ABA oxidation with its end products of phaseic acid (PA) and dihydrophaseic acid (DPA) (Cutler and Krochko 1999), but in conifers such as Douglas-fir, the dominant product of ABA catabolism in long shoots is ABA glucose ester (ABA-GE) (Kong et al 2008(Kong et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Abscisic acid negatively modulates the effect of other plant hormones, such as GAs (Tompsett 1977) and auxin (Weiss and Ori 2007). This is of interest in conifers, because exogenously applied GA has been proven to be an effective stimulant of cone formation (Ross 1983;Pharis and King 1985;Smith and Greenwood 1995;Kong et al 2008). The main ABA catabolic pathway in many higher plants is ABA oxidation with its end products of phaseic acid (PA) and dihydrophaseic acid (DPA) (Cutler and Krochko 1999), but in conifers such as Douglas-fir, the dominant product of ABA catabolism in long shoots is ABA glucose ester (ABA-GE) (Kong et al 2008(Kong et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Although Wheeler et al (1985) found a 28 % increase in the number of cones per tree by adding Ca(NO 3 ) 2 to a girdling treatment, this increase was not statistically significant. Although there is ample evidence to conclude that nitrogen fertilization enhances flowering of Douglas-fir (Ebell 1972;Masters 1982;Wheeler et al 1985;Stoate et al 1962), responses to fertilization are inconsistent in Douglas-fir and other conifers, with weather conditions potentially playing an important role (Ebell 1972;Smith and Greenwood 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural treatments may perform poorly when trees are not physiologically predisposed to flower (a condition that may be overcome by applications of GA) or when weather conditions are unfavorable (Smith and Greenwood 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It can alter the morphology, growth, root distribution, and architecture of the plant, and even increase the tolerance of the plant to abiotic stress (Mashela and Nthangeni, ; Chen et al , ; Chen et al , ). It was reported that a combination of root cutting and gibberellin A increases reproductive bud production in the conifer Picea mariana (Smith and Greenwood, ). Root redistribution via root cutting in agroforestry systems has confirmed that root cutting can serve as a potential tool for managing belowground competition when trees and crops are grown together (Wajja‐Musukwe et al , ).…”
Section: Introductionmentioning
confidence: 99%